Communicative competence update of public school EFL teachers in Santarém-PA: an account of experience in a university extension project - Tanaka, Elder Koei Itikawa; Hitotuzi, Nilton Varela; Hall, Silvia Cristina Barros de Souza; Ferro, Paola Piovezan (BELT - Brazilian English Language Teaching Journal, 2018)
This article reports the experience of supervisors, collaborators and volunteers with the extension project “Atualização de Competência Comunicativa em Língua Inglesa” (Communicative Competence in English Update), executed in 2018 at the University of Western Pará (UFOPA). It is a free update course offered to public school EFL teachers of Santarém, Pará, with two distinct but complementary goals: firstly diminish gaps in the qualification of these professionals caused by the incipient offer of these kind of courses in the city; secondly offer students of the English Licensure at UFOPA the opportunity to teach. After a brief description of the project and the motivation behind it, we will present an analysis of the dynamics between students and teachers throughout the course, as well as the project’s results.